A Multimodal Diagnostic Approach to Liver Mass, Including Clinical, Radiological and Pathological Parameters - Faisal Rahman, Mubasher Ahmad, Nosheen Khurram, Fareeha Naseer Syed, Ayesha Kamran, Rukhsana Gulzar, Rida Fatima (Pakistan Journal of Medical & Health Sciences, 2023)
Liver masses encompass a wide spectrum of benign and malignant lesions, posing significant diagnostic and therapeutic challenges in clinical practice. Place of Study: This study aimed to evaluate the clinical, radiological, and pathological characteristics of liver masses in University College of Medicine & Dentistry Lahore emphasizing the importance of a multidisciplinary approach for accurate diagnosis and management. Study Duration: January 2021-December 2022 Methodology: A retrospective analysis was conducted on 200 patients with liver masses referred between 2020 and 2023. Data on clinical history, imaging findings, histopathology, and serum biomarkers were collected and analyzed. Result: Hepatocellular carcinoma (HCC) was the most common malignant lesion (45%), followed by metastatic tumors (30%), while benign lesions such as hemangiomas (20%) and focal nodular hyperplasia (FNH) (15%) were also prevalent. Radiological imaging, including ultrasound, CT, and MRI, played a pivotal role in lesion characterization, with MRI demonstrating superior diagnostic accuracy. Discussion: Histopathological examination confirmed diagnoses, with immunohistochemistry aiding in differentiating malignant lesions. Serum biomarkers, such as alpha-fetoprotein (AFP), carcinoembryonic antigen (CEA), and carbohydrate antigen 19-9 (CA 19-9), provided additional diagnostic value. The study underscores the necessity of integrating clinical, radiological, and pathological data to optimize patient outcomes. Early detection, accurate diagnosis, and tailored treatment strategies are critical for improving prognosis, particularly in malignant liver masses. Conclusion: The findings advocate for a multidisciplinary approach involving gastroenterologists, radiologists, pathologists, oncologists, and surgeons to address the complexities of liver mass evaluation and management. This integrated framework not only enhances diagnostic precision but also guides personalized therapeutic interventions, ultimately improving patient care. Keywords: Hepatocellular carcinoma (HCC), Metastatic tumors, Hemangiomas, Focal nodular hyperplasia (FNH), Radiological imaging (ultrasound, CT, MRI), MRI diagnostic accuracy